2023
DOI: 10.17816/cp3728
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Depression with Vortioxetine and Second Generation Antipsychotics During the Period of Remission Formation in Schizophrenia (Interim Data Analysis)

Abstract: BACKGROUND: Depression in patients with schizophrenia worsens the course of the disease by increasing the risk of suicide, by complicating the clinical picture of the disorder, and by reducing the quality of the social functioning; its treatment is difficult, since monotherapy, even when involving modern antipsychotics, does not always prove successful. While the prescription of additional antidepressants (ADs) can improve the likelihood of a better outcome, the effectiveness of such augmentation in many cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…A group of studies dealt with vortioxetine use in psychiatric diagnoses other than unipolar depression (n = 7). These articles report encouraging results in the treatment of negative, cognitive and affective symptoms of schizophrenia [108][109][110], along with preliminary effectiveness in bipolar depression [111], burning mouth syndrome [112], postmenopausal depression [113], and panic disorder [114]. A further group of studies (n = 5) demonstrated that vortioxetine treatment is associated with affective and cognitive symptoms amelioration in patients with neurological conditions, including neurocognitive decline [115][116][117], Parkinson's disease [118], and post-stroke depression [119].…”
Section: Analytical Observational Studiesmentioning
confidence: 98%
“…A group of studies dealt with vortioxetine use in psychiatric diagnoses other than unipolar depression (n = 7). These articles report encouraging results in the treatment of negative, cognitive and affective symptoms of schizophrenia [108][109][110], along with preliminary effectiveness in bipolar depression [111], burning mouth syndrome [112], postmenopausal depression [113], and panic disorder [114]. A further group of studies (n = 5) demonstrated that vortioxetine treatment is associated with affective and cognitive symptoms amelioration in patients with neurological conditions, including neurocognitive decline [115][116][117], Parkinson's disease [118], and post-stroke depression [119].…”
Section: Analytical Observational Studiesmentioning
confidence: 98%